2006
DOI: 10.1182/blood-2005-09-3775
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent cellular cytotoxicity (ADCC) is mediated by genetically modified antigen-specific human T lymphocytes

Abstract: IntroductionThe potential of transfused T lymphocytes as potent immune effectors is well documented. Such a potential was initially discovered in the allogeneic context from the clinical outcome of patients who received bone marrow transplants, where unselected donor T lymphocytes transfused together with hematopoietic precursors were found to be responsible for the graft-versus-host reaction as well as the graft-versus-leukemia effect. 1 Manipulation of this allogeneic effect through infusion of donor lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
85
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 61 publications
0
85
1
Order By: Relevance
“…The former two cellular outputs directly accounted for tumoricidal activity, and the latter two cellular activities were able to contribute to the durable antitumor effect observed in vivo. To our knowledge, no previous reports describing a similar concept have included in vivo experimental observations (18,34). Therefore, after confirming that rituximab-induced CDC was not present in NOG mouse serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former two cellular outputs directly accounted for tumoricidal activity, and the latter two cellular activities were able to contribute to the durable antitumor effect observed in vivo. To our knowledge, no previous reports describing a similar concept have included in vivo experimental observations (18,34). Therefore, after confirming that rituximab-induced CDC was not present in NOG mouse serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these effector cells could be used in combination with almost all currently available ADCC-mediating anticancer mAbs. A similar concept was proposed by Cl emenceau and colleagues (18), who validated in vitro the applicability of CD3 þ T cells gene-modified to express a FcgRIIIa-158(V/V)-FceRIg chimeric receptor for ADCC against CD20 þ lymphoma cells in combination with rituximab, although the in vivo validation has not been described yet. Regarding the risk of leukemogenesis of infused gene-modified T cells, results from clinical trials using retroviral or lentiviral vector gene-modified T cells for adoptive cell therapy have proved the long-term safety of this approach (19,20).…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, in side-to-side comparisons with a chimeric receptor containing the more common F158 variant, the CD16V-BB-z had a significantly higher capacity to bind human Ig Fc, and induced more vigorous proliferation and cytotoxicity, evoking results of recent studies addressing the role of affinity in chimeric antigen receptor function (42,43). Clemenceau and colleagues described a receptor containing the CD16 158V combined with the transmembrane and cytoplasmic domains of FceRIg, and found that selected Tcell clones expressing this receptor could lyse Epstein-Barr virus derived B-lymphoblastoid cells in the presence of rituximab (40). Current "second generation" chimeric receptors combine a stimulatory molecule with a costimulatory one to augment signaling and prevent activation-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The 1H11-34 cell line is a T cell hybridoma specific for HEL [107][108][109][110][111][112][113][114][115][116] presented by I-E d (17). Activated human T cells transduced with the retroviral vector encoding human Fc␥RIIIA-FcR␥ chimera were generated, as described previously (18).…”
Section: Cell Lines and Micementioning
confidence: 99%